T-regulatory cell/T helper 17 cell imbalance functions as prognostic biomarker of oral squamous cell carcinoma – CONSORT. Issue 49 (4th December 2020) - Wang, Lin; Zhang, Yingjie; Xie, Fuqiang
Abstract: Background: The role of T cells in the pathogenesis of oral squamous cell carcinoma (OSCC) was clarified by examining the levels of differentiated CD4 + CD25 + FOXP3 + T-regulatory cells (Treg cells) and CD4+IL17+ T helper 17 (Th17) cells in OSCC patients. Methods: Flow cytometry was conducted to measure the proportions of Treg/Th17 cells in different sample groups to identify a proper maker indicative of the progression and prognosis of OSCC. Results: The results showed that a higher Treg/Th17 ratio led to poorer prognosis. Also, the proportions of both Treg cells and Th17 cells were significantly elevated in OSCC patients compared with those in the control groups, suggesting a correlation between Treg/Th17 imbalance and the prognosis of OSCC. Furthermore, the ratios of Treg/Th17 cells in OSCC patients differed at different time points of cancer progression. For example, stage III-IV patients showed the most evident increase in the Treg/Th17 ratio, while the Treg/Th17 ratio in control subjects was the lowest. Conclusions: Therefore, a higher ratio of Treg/Th17 indicated the progression of OSCC and a larger tumor size. Therefore, Treg and Th17 imbalance was implicated in OSCC progression.